Kansas Youth Water Advocates Conference Report - Bohnenblust, Katelyn (My University, 2017)
Kansas is a state in need of more water conservation and education efforts. A team of several state agencies developed the Long-Term Vision for the Future of Water Supply in Kansas, addressing the issue of water depletion in our state. The vision includes a mission, goals, and action items, with one of them being the need for education and outreach. The Education and Public Outreach Supplement of the Vision specifically states, “Increase awareness and knowledge of Kansas youth on water-related issues through K-12 education and beyond-the-classroom opportunities” and “Develop partnerships between industry, community, and educational institutions that will promote and train for water-related careers.” Action items directly stated in the supplement include, “Collaborate with youth-related organization leadership on water-related educational opportunities and establish sessions and experiences focused on water” and “Develop workshops and professional developments based on information found in KDA Agriculture Workforce Needs Assessment and state meetings.” Kansas Youth Water Advocates Conference worked to meet the need addressed in the Long-Term Vision for the Future of Water Supply in Kansas. The Vision for the Future of Water Supply in Kansas (Vision) validated the need of a youth water education conference. This conference sought to train a group of highly motivated high school agricultural education students to disseminate key information about water use and conservation efforts to communities across the State. Students who attended the conference became experts on water issues affecting the state and will help educate their communities about how they can help conserve and protect our water resources. I partnered with Dr. Gaea Hock of Kansas State University and Susan Metzger of the Kansas Department of Agriculture to coordinate this conference this summer and will continue to serve as the undergraduate mentor for the high school students over the entire year. My duties included assisting with writing conference curriculum, conference planning, activities, logistics, coordinating with the program manager to secure expert speakers, and recruiting program participants. The Kansas Department of Agriculture, surrounding states, and high school agricultural education teachers are all tracking the implementation and success of this training. Investing in young adults who will become the next generation of experts on water issues affecting the state is crucial because water and the Kansas economy are directly linked. According to the KDA, the Ogallala aquifer adds $7 billion to the western Kansas economy. The ability to maintain irrigated agriculture and livestock production in western Kansas is directly linked to a community’s ability to maintain its schools, hospital, and other critical quality of life elements. These youth will help educate their communities about how they can help conserve and protect our water resources so that the livelihood of Kansas families does not deteriorate.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Bohnenblust, K. (2017). Kansas Youth Water Advocates Conference Report. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: 9-12 education; Water advocacy; Kansas Students; Kansas Water Resources; Long term vision; Water conservation; Education, Secondary; Water conservation; Water-supply; Kansas; Students; Resource allocation; Reports